Supportive Care Needs Among Breast Cancer Patients Undergoing Chemotherapy in Gorontalo - Amalia , Lia; Wulansari, Ika; Yusuf , Nur Ayun R.; Haji Jafar, Cindy Puspita Sari (Journal of Health and Nutrition Research, 2025)
Breast cancer patients undergoing chemotherapy often experience significant side effects that impact their physical and psychosocial well-being, necessitating a clear understanding of their supportive care needs for effective patient management. This study aimed to describe the supportive care needs among breast cancer patients undergoing chemotherapy at a regional public hospital in Gorontalo, Indonesia. A descriptive cross-sectional study was conducted involving 38 breast cancer patients undergoing chemotherapy at RSUD Prof. Dr. H. Aloei Saboe, recruited via consecutive sampling. Supportive care needs were assessed using the Supportive Care Needs Survey Short Form 34 (SCNS-SF34). The data were analyzed descriptively using frequency distributions to determine the proportion of patients reporting unmet needs in various domains. The highest prevalence of unmet supportive care needs was identified in the physical domain, with 57.9% (n=22) of respondents indicating a need for support. Lower levels of unmet needs were reported for the psychological domain (39.5%, n=15 needing support), the sexual domain (23.7%, n=9 needing support), and the information domain (13.2%, n=5 needing support). Notably, no respondents (0%) reported unmet needs in the care support domain, indicating this aspect of care was perceived as thoroughly met. Physical symptoms represent the most prominent area of unmet supportive care needs for breast cancer patients undergoing chemotherapy in this Gorontalo hospital setting. While care support appears satisfactory, targeted interventions focusing on managing physical side effects are crucial for improving patient well-being during treatment.